Evaluating sustainable building assessment systems: a comparative analysis of GBRS and WBLCA - Anyanya, Daniel; Paulillo, Andrea; Fiorini, Silvia; Lettieri, Paola (Frontiers in Built Environment, 2025)
This comprehensive review examines sustainable building assessment systems, focusing on Green Building Rating Systems (GBRS) like BREEAM and Whole Building Life Cycle Assessment (WBLCA) approaches in the context of achieving the United Kingdom’s climate targets. The study highlights significant limitations in GBRS, particularly their inadequate focus on embodied carbon emissions and alignment with national climate goals. WBLCA emerges as a promising solution, offering a holistic methodology for quantifying environmental impacts across a building’s entire lifecycle. The research explores the integration of advanced techniques such as Building Information Modelling (BIM), automated data collection, and artificial intelligence to enhance WBLCA’s effectiveness. While WBLCA shows potential in driving the built environment sector towards climate targets, the study identifies challenges including methodological issues, data quality, and the need for standardisation. This article emphasises the importance of aligning building assessment systems with national climate targets and carbon budgets. It concludes by calling for a paradigm shift from static, point-based rating systems to dynamic, quantitative approaches in sustainable building assessment, highlighting the need for interdisciplinary collaboration and education to support this transition.